Bipolar Electrochemical Approach with a Thin Layer of Supporting Electrolyte towards the Growth of Self‐Organizing TiO2 Nanotubes. Issue 3 (21st July 2015) - Saqib, Muhammad; Lai, Jianping; Zhao, Jianming; Li, Suping; Xu, Guobao
Abstract: We report a new bipolar electrochemical approach for the growth of ordered titanium dioxide nanotubes (NTs), using a thin layer of supporting electrolyte, and the preparation of multiple samples through bipolar electrochemistry in a single wireless run. Our configuration allows the efficient growth of TiO2 NTs in a horizontal direction with low electrolyte consumption, which facilitates heat dissipation. In this simple, rapid, and cost‐effective method, we can also successfully tune the inner and outer diameters of TiO2 NTs to 25–64 nm and 42–85 nm, respectively, with key parameters such as fluoride content, anodization voltage, anodization time, and water content. Abstract : Bipolar tuning : A new bipolar electrochemical approach enables rapid and wireless growth of self‐organized TiO2 nanotubes (NTs) with tunable diameter and morphology by using a thin layer of electrolyte. The simple, rapid, and cost‐effective preparation of multiple samples in a single wireless run is shown for the first time. Different crucial parameters are optimized to tune the diameter in the range of 25–85 nm, as rapid tuning of TiO2 NTs properties markedly increases its potential applications.